Multi agent system for distributed management of microgrids - Eddy Foo, Yi Shyh; Gooi, Hoay Beng; Chen, Shuai Xun (2015 IEEE Power & Energy Society General Meeting, 2015)
Summary form only given: In market operations, Distributed Generators (DGs) and price-sensitive loads participate in a microgrid energy market implemented in JADE. Each DG and each price-sensitive load is represented by the respective agents which perform various functions such as scheduling, coordination and market clearing subject to system, DG and load constraints. Each agent is assigned to one of the several agent objectives which maximizes either DG or load surpluses or both. In simulated operation of a microgrid, hourly power reference signals and load control signals from JADE are passed to DG and load models developed in MATLAB/Simulink using MACSimJX. Simulated operation of DGs and loads are studied by performing simulations under different agent objectives. Results from simulation studies demonstrate the effectiveness of implementing multi agent system (MAS) in the distributed management of microgrids.